Overview of the physics design of the EHL-2 spherical torus - LIANG, Yunfeng; XIE, Huasheng; SHI, Yuejiang; GU, Xiang; JIANG, Xinchen; DONG, Lili; WANG, Xueyun; YANG, Danke; LIU, Wenjun; SUN, Tiantian; WANG, Yumin; LI, Zhi; et al. (Plasma science & technology, 2025)
ENN is planning the next generation experimental device EHL-2 with the goal to verify the thermal reaction rates of p- 11 B fusion, establish spherical torus/tokamak experimental scaling laws at 10’s keV ion temperature, and provide a design basis for subsequent experiments to test and realize the p- 11 B fusion burning plasma. Based on 0-dimensional (0-D) system design and 1.5-dimensional transport modelling analyses, the main target parameters of EHL-2 have been basically determined, including the plasma major radius, R 0 , of 1.05 m, the aspect ratio, A , of 1.85, the maximum central toroidal magnetic field strength, B 0 , of 3 T, and the plasma toroidal current, I p , of 3 MA. The main heating system will be the neutral beam injection at a total power of 17 MW. In addition, 6 MW of electron cyclotron resonance heating will serve as the main means of local current drive and MHD instabilities control. The physics design of EHL-2 is focused on addressing three main operating scenarios, i.e., (1) high ion temperature scenario, (2) high-performance steady-state scenario and (3) high triple product scenario. Each scenario will integrate solutions to different important issues, including equilibrium configuration, heating and current drive, confinement and transport, MHD instability, p- 11 B fusion reaction, plasma-wall interactions, etc. Beyond that, there are several unique and significant challenges to address, including establish a plasma with extremely high core ion temperature ( T i,0 > 30 keV), and ensure a large ion-to-electron temperature ratio ( T i,0 / T e,0 > 2), and a boron concentration of 10%‒15% at the plasma core; realize the start-up by non-inductive current drive and the rise of MA-level plasma toroidal current. This is because the volt-seconds that the central solenoid of the ST can provide are very limited; achieve divertor heat and particle fluxes control including complete detachment under high P / R (> 20 MW/m) at relatively low electron densities. This overview will introduce the advanced progress in the physics design of EHL-2.